Management missed canal tooth and broken file using ultrasonic instrument - Abiddinda; Agustin, Wandita Swasti; Rinastiti, Margareta; Ratih, Diatri Nari (Dental Journal (Majalah Kedokteran Gigi), 2023)
Background: Endodontic mishaps, such as missed canal and broken file, are procedural accidents that can affect the prognosis of endodontic treatment. A missed canal can lead to endodontic failure because of bacterial remnants in the root canal. A broken file may cause obstruction of the canal, inhibiting the process of shaping and cleaning. An ultrasonic instrument can be used under a dental microscope to manage a missed canal or broken file fragment. Purpose: This study aimed to show the management of missed canal and instrument separation by endodontic retreatment using an ultrasonic instrument under dental microscope. Case: A 31-year-old female patient presented to Dental Hospital Universitas Gadjah Mada with discomfort from chewing her upper left molar since 2 weeks (January 4, 2022). The tooth was subjected to root canal treatment 2 years ago (November 18, 2019). The percussion test yielded a positive result. The examination of radiographs showed the presence of a broken file in the middle third of the mesiobuccal root canal. Case Management: The first stage of the retreatment was removal of the gutta-percha. This was followed by exploration of the missed canal and retrieval of the broken file using an ultrasonic instrument under a dental microscope. Then, the root canals, including the messiobuccal2 canal, that was missed at the previous treatment, were prepared. The final step was zirconia crown restoration with a fiber post. Conclusion: An ultrasonic device along with a dental microscope can be used to manage a missed canal and instrument separation conservatively.